2016
DOI: 10.1051/matecconf/20167602006
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Management Systems and Sustainability in SMEs

Abstract: Abstract. Environmental sustainability in manufacturing sector has been allocated a major consideration in the international literature. Due to growing concerns over the high effect of SMEs on world manufacturing industries and their contribution to pollution; this research attempts to focus on the key parameters that interact in the application of environmental management system, taking into account the main features of SMEs and also the integral role of industrial entrepreneurs in inspiring their firms' appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
1
9
0
1
Order By: Relevance
“…SMEs may be as high as 60-70% of global environmental pollution. This statements are in accordance with findings ofShah, Ganji, & Hasan (2016) who reported that SMEs share 70% of global pollution, with the majority of manufacturing sector. Therefore, reducing the environmental impact of SMEs in both manufacturing and services is a key factor in successfully greening the economy(OECD, 2015).…”
supporting
confidence: 93%
“…SMEs may be as high as 60-70% of global environmental pollution. This statements are in accordance with findings ofShah, Ganji, & Hasan (2016) who reported that SMEs share 70% of global pollution, with the majority of manufacturing sector. Therefore, reducing the environmental impact of SMEs in both manufacturing and services is a key factor in successfully greening the economy(OECD, 2015).…”
supporting
confidence: 93%
“…Moreover, SMEs play a significant role on enterprise scenes and market economies, as they cover about 90% of all global businesses, with the high number of suppliers through the supply chain. Not surprisingly, they contribute to 70% of the environmental pollution within the manufacturing sector [1]. Therefore, executing SCM practices, SMEs can achieve significant benefits.…”
Section: A Adoption Of Supply Chain Management (Scm)mentioning
confidence: 99%
“…Regarding the for-profit organisations, a research paper examines the influence of stakeholder's pressures towards environmental sustainability of an adhesive manufacturing industry through a qualitative survey [22]. As reported, again competitive advantage plays a vital role in this case as a critical motivator.…”
Section: For-profit and Non-profit Organisationsmentioning
confidence: 99%
“…Furthermore, high industry competition and shareholders' inspiration exert the most important influential factors for environmental management system (EMS) adoption. The shareholder's desire is due to the fact that the factors such as financial performance, energy and water consumption and recycling are their major business challenges, and hence, move them towards adoption of sustainable practices [22].…”
Section: For-profit and Non-profit Organisationsmentioning
confidence: 99%